FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN - SETYOPRATIGNJO, RM. LISTIJONO (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study investigates the influence of two main factors, namely Training and Work Motivation, on the productivity of work of employees of PT. Cipta Jaya Kreasi in West Java. The free variable in this study is Training and Work Motivation, and the bound variable is Employee Work Productivity. The study was conducted on 50 respondents who worked at the company. This research used quantitative data obtained directly through a questionnaire. The research hypothesis was tested using double linear regression analysis, performed using the Statistical Package for the Social Sciences, or SPSS, version 20. The results of this study show that training has a positive and significant impact on work productivity, and work motivation has a significant and positive impact on employee work productiveness.